2006
DOI: 10.22358/jafs/70131/2006
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the capability of the rumen bacterium, <i>Butyrivibrio fibrisolvens</i>, to utilize fructose polymers for growth

Abstract: The rumen bacterium Butyrivibrio fibrisolvens was able to grow in vitro when timothy grass fructan, inulin, inulooligosaccharides, sucrose, or fructose was the sole source of carbon in the culture medium, and utilized 89.9, 47.7, 80.9, 87.9 and 94.5% of the carbohydrate, respectively. The distinctly lower utilization of inulin than other carbohydrates was accompanied by a considerably lower bacteria count in the cultures. Examination of an extract from bacterial cells showed that its fructanolytic activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A similar relationship was found in the case of two other strains of ruminal treponemes from our collection (Kasperowicz, 2005). In contrast to the mentioned strains of treponemes, the carbohydrates added to the culture medium visibly induced the synthesis of relevant fructanolytic enzymes by Butyrivibrio fi brisolvens, suggesting their inducible character (Cendrowska et al, 2006). Thus, the nature of synthesis of the fructanolytic enzymes seems be species specifi c in the case of the mentioned bacteria.…”
Section: Discussionmentioning
confidence: 87%
“…A similar relationship was found in the case of two other strains of ruminal treponemes from our collection (Kasperowicz, 2005). In contrast to the mentioned strains of treponemes, the carbohydrates added to the culture medium visibly induced the synthesis of relevant fructanolytic enzymes by Butyrivibrio fi brisolvens, suggesting their inducible character (Cendrowska et al, 2006). Thus, the nature of synthesis of the fructanolytic enzymes seems be species specifi c in the case of the mentioned bacteria.…”
Section: Discussionmentioning
confidence: 87%
“…We found that Butyrivibrio , Blautia , Oscillospira , and Odoribacter , genera known to contain a series of butyrate-producing bacteria, are all enriched in participants within Q1 of GLA and participants without type 2 diabetes. These bacteria have been reported to have the ability to use fructose or glucuronate and were inversely associated with obesity ( 26 30 ). Moreover, in our study, Blautia , Oscillospira , and Odoribacter were inversely associated with circulating triglycerides, which were found to be positively associated with type 2 diabetes and higher level of GLA ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the FAO/WHO (2002), prebiotics are non-digestible substances that provide a beneficial physiological effect on the host by selectively stimulating the favorable growth or activity of a number of indigenous bacteria. In ruminants there are evidence that prebiotics increase the population of ciliated protozoa in the rumen (Cendrowska et al, 2006), decrease ammonia nitrogen (NH3-N) concentration (Shibata, 1985;Biggs and Hancock, 1998), increase volatile fatty acid (VFA) and microbial protein concentrations, and stabilize the rumen pH (Li et al ., 2007). It is possible that, due to the fact that some prebiotics might not be degraded in the rumen, these functional carbohydrates could reach the large intestine intact where they could have beneficial effects.…”
Section: Introductionmentioning
confidence: 99%